L'estructura argumental dels noms en català = Argument structure of nouns in Catalan - Cremades Cortiella, Elga, 1987- (Spisy Masarykovy univerzity v Brně, Filozofická fakulta, 2017)
"This book analyzes the structure of noun phrases in Catalan from a theoretical and descriptive perspectives, with the main purpose of determining and systematizing the properties of the argument structure of nominals in Catalan. It also intends to offer a general view of its syntactic materialization in Catalan and to offer some explanation to the main regular patterns. The main question of this research, "How do nominal arguments in Catalan syntactically materialize?" implies having to answer to three secondary questions: "Which are the nouns that admit arguments in Catalan?", "How are nominal arguments realized in Catalan? What do realizations depend on?", and "What is the order of the argument complements of the nouns when more than one argument appears in the same phrase?". To solve these enquiries, the author analyzed from more than 200 nouns, which was obtained from the Textual computerized corpus of the Catalan (Corpus textual informatitzat de la llengua catalana - CTILC)."--Publisher's website